Sources of growth in Sub-Saharan-African countries - BEZE, Eyayaw Teka (KDI School, 2015)
This paper examines the sources of growth in Sub-Saharan African countries, using the growth accounting framework and estimate aggregate production function by analyzing Penn World Tables (version 8.1) data of over 30 years. In addition, it compares the sources of growth for subgroups and sub-periods. The overall performance of the SSA region was not impressive during 1980-2011 period, output grew by 3.7 percent while per capita GDP grew by 0.8, reflecting the region being victim of prolonged conflicts and civil wars. Capital deepening has contributed 0.2 percent points to the growth of per worker output. Factor accumulation accounted 3.1 percentage points for output growth while TFP accounted 0.6 percent for output growth over the entire period. As the results show it turns out that average real GDP growth in the region during 1980-2011 was mainly driven by factor accumulation with modest role for TFP. Unlike in the previous studies, TFP constitutes a bigger portion of per capita output growth in the region, it accounts 75 percent (0.6 out of 0.8 percentage points) for the per capita output growth although human capital effect is the whole reason for the growth of TFP. Therefore, the old image of TFP being nil in the region is not correct anymore. In addition, TFP improvements have been changing differently across time periods and subgroups. It has kept increasing overtime. On average the growth of TFP was negative in the first decade, 1980-1990, (i.e., -0.1 percent), but it grew positively thereafter in the rest decades. Without a separate account of TFP and human capital, the growth of TFP was 0.4 percent in 1991-2001 and 1.4 percent in 2002-2011 period. At the subgroup level as well TFP has shown a positive trend overtime. On average, low income countries have experienced lesser TFP growth (0.4 percent) than all the other subgroups, and high income group (Equatorial Guinea) took the lead with 3.8 percentage TFP growth during the entire period.
Thesis(Master) --KDI School:Master of Development Policy,2015